The museums and their public: a study in the National Museum of Fine Arts of Cuba (MNBA) (Cadernos de Sociomuseologia, 2020)
The present communication is inserted within the studies of museum audiences that delve into the symbolic meanings of people and takes as a basis the concept of cultural consumption. For this reason, the theme approaches the consumption of Cuban artistic heritage by young audiences, through the temporary exhibitions of the National Museum of Fine Arts (MNBA). The starting point was the scientific question: What is the consumption of Cuban artistic heritage in young audiences of the temporary exhibitions of the Cuban Art Building of the MNBA, which determine the practices and discourses regarding this heritage? The objective is to explain the impact that the valuations, meanings, stereotypes and uses of the Cuban artistic heritage of young audiences have on the practices and discourses regarding this heritage, through the temporary exhibitions of the Cuban Art Building of the MNBA. The methodology used qualitative approach methods and techniques such as the survey, the discussion group and the completion of sentences, to reach the conclusions that practices and discourses regarding artistic heritage vary according to different young audiences: discourses can be traditional, more up-to-date or marked by the symbolic-affective element and; practices, are determined by stereotypes that last in young people.Keywords: study of audiences, cultural consumption, artistic heritage, young audiences, temporary exhibitions